Navigating a Path of Uncertainty: Profiling Novice Teachers as Adaptive Leaders - Edwin Darrell De Klerk; June Monica Palmer (IAFOR Journal of Education)
Increasingly, novice teachers function in complex learning environments that require heightened resilience and making calculated, sometimes unexpected decisions. Undoubtedly, novice teachers in the African context must adapt to the persistent weaknesses of inadequate education systems, characterized by underperforming learners, high learner drop-out rates, limited resources, and possible un-employability after completing their studies. In exploring the realities of novice teachers in two provinces of South Africa, this paper aimed to understand how novice teachers’ adaptive leadership ability can support them in transforming their schools during challenging times. An adaptive leadership profiling framework is conceptualized, according to the novice teachers’ portrayal of their adaptive leadership ability during uncertain and challenging times. Novice teachers’ narratives and semi-structured interviews informed the qualitative data collection process. An interpretative phenomenological analysis was conducted to analyze the data. The findings revealed that novice teachers desire an enabling leadership environment in which they can contribute meaningfully to improving their schools. Novice teachers echoed concern about the creation of a psychologically safe environment in which to function, while they are engaging in a process of sense-making of their realities. Finally, novice teachers’ contributions to sustainable change must be acknowledged, while leadership strategies must be explored to overcome the adaptive challenges they face.